2020
DOI: 10.1371/journal.pone.0236674
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and QTL mapping for multiple biotic stress resistance in cassava

Abstract: In Sub-Saharan Africa cassava (Manihot esculenta Crantz) is one of the most important food crops where more than 40% of the population relies on it as their staple carbohydrate source. Biotic constraints such as viral diseases, mainly Cassava Mosaic Disease (CMD) and Cassava Brown Streak Disease (CBSD), and arthropod pests, particularly Cassava Green Mite (CGM), are major constraints to the realization of cassava's full production potential in Africa. To address these problems, we aimed to map the quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“… Masumba et al (2017) detected two highly significant CMD resistance QTLs on chromosome 12 defining the CMD2 locus, as well as additional putative QTLs on other chromosomes. Similar observations were made by Garcia-Oliveira et al (2020) who found two closely linked loci on chromosome 12 and additional QTLs on chromosomes 9 and 10. Further dissection of the major QTL on chromosome 12 ( Manihot esculenta v5.1 and 6.1 genome assembly) revealed the presence of two possible epistatic loci and/or multiple resistance alleles, which may account for the difference between moderate and strong disease resistance in the germplasm ( Masumba et al, 2017 ; Nzuki et al, 2017 ; Garcia-Oliveira et al, 2020 ; Table 2 ).…”
Section: Connecting Genotypic and Phenotypic Information And Discoversupporting
confidence: 85%
See 4 more Smart Citations
“… Masumba et al (2017) detected two highly significant CMD resistance QTLs on chromosome 12 defining the CMD2 locus, as well as additional putative QTLs on other chromosomes. Similar observations were made by Garcia-Oliveira et al (2020) who found two closely linked loci on chromosome 12 and additional QTLs on chromosomes 9 and 10. Further dissection of the major QTL on chromosome 12 ( Manihot esculenta v5.1 and 6.1 genome assembly) revealed the presence of two possible epistatic loci and/or multiple resistance alleles, which may account for the difference between moderate and strong disease resistance in the germplasm ( Masumba et al, 2017 ; Nzuki et al, 2017 ; Garcia-Oliveira et al, 2020 ; Table 2 ).…”
Section: Connecting Genotypic and Phenotypic Information And Discoversupporting
confidence: 85%
“…Similar observations were made by Garcia-Oliveira et al (2020) who found two closely linked loci on chromosome 12 and additional QTLs on chromosomes 9 and 10. Further dissection of the major QTL on chromosome 12 ( Manihot esculenta v5.1 and 6.1 genome assembly) revealed the presence of two possible epistatic loci and/or multiple resistance alleles, which may account for the difference between moderate and strong disease resistance in the germplasm ( Masumba et al, 2017 ; Nzuki et al, 2017 ; Garcia-Oliveira et al, 2020 ; Table 2 ). Gaps in the pseudochromosome 12 region containing the CMD2 loci caused by highly repetitive DNA might explain the two separate loci ( Kuon et al, 2019 ).…”
Section: Connecting Genotypic and Phenotypic Information And Discoversupporting
confidence: 85%
See 3 more Smart Citations